2016
DOI: 10.1007/s11356-016-8117-8
|View full text |Cite
|
Sign up to set email alerts
|

An integrated assessment of pollution and biological effects in flounder, mussels and sediment in the southern Baltic Sea coastal area

Abstract: Organic and metal contaminants and biological effects were investigated in flounder, mussels, and sediments in the southern Baltic Sea coastal area in order to assess environmental quality status in that area. Four sites were selected, including two within the Gulf of Gdańsk (GoG). In biota and sediment at each site, DDTs dominated over PCBs and PBDEs were the least abundant among organic contaminants. Their concentrations decreased progressively outward from GoG. Among metal contaminants, the levels of Hg, Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In the present paper, the Cd concentrations in muscle were moderate comparatively to the heavily polluted Gulf of Gdansk in southern Baltic Sea [17] (flounder muscle: Cd 0.004 µg g −1 dry wt. ), and the levels of Pb and Zn were rather similar to those in the Baltic Sea (flounder muscle: Pb 0.04; Zn 20 µg g −1 dry wt.…”
Section: Chemical Contamination and Hypothesis On The Flounder Use Of Habitat In The Seine Estuary And Douarnenez Baymentioning
confidence: 44%
See 2 more Smart Citations
“…In the present paper, the Cd concentrations in muscle were moderate comparatively to the heavily polluted Gulf of Gdansk in southern Baltic Sea [17] (flounder muscle: Cd 0.004 µg g −1 dry wt. ), and the levels of Pb and Zn were rather similar to those in the Baltic Sea (flounder muscle: Pb 0.04; Zn 20 µg g −1 dry wt.…”
Section: Chemical Contamination and Hypothesis On The Flounder Use Of Habitat In The Seine Estuary And Douarnenez Baymentioning
confidence: 44%
“…Furthermore, the sum of the major PCB detected in Seine flounder muscle (472 ng g −1 dry wt) was considerably higher than those observed in Baltic Sea polluted sites (15 < 7 PCB < 34 ng g −1 dry wt. ; [17]).…”
Section: Chemical Contamination and Hypothesis On The Flounder Use Of Habitat In The Seine Estuary And Douarnenez Baymentioning
confidence: 99%
See 1 more Smart Citation
“…However, BPA has also been used in the fabrication of plastic bottles, dental prosthetics, thermal paper, food storage containers found in the home and more [6,7,51]. It may also be found as an environmental pollutant, which may contaminate drinking water as well as any seafood harvested from contaminated ocean waters [3,14,16]. The health effects are wide ranging and especially seem to impact the development of children and young adults, the reproductive system, and the immune system, which may lead to carcinomas [45].…”
Section: Introductionmentioning
confidence: 99%
“…There has also been a recent German study that found the coastal waters of Latvia to be contaminated with bisphenol and several other compounds. 63 Again that study was based in Germany. There are two EU member states that have no published articles concerning bisphenol research.…”
Section: Bisphenol Research In the Rest Of The Lesser Developed Eu Mementioning
confidence: 99%